Effects of sea water and herbicide for salt toelarnt weed mangement in turfgrass - Uddin, Md Kamal; Juraimi, Abdul Shukor; O., Radziah; Anwar, Md Parvez (Bangladesh Botanical Society, 2017)
Sea water in combination with trifloxysulfuron-sodium and quinclorac were used to observe weed injury level in turfgrass field. The weed species viz., Sporobolus diander (L.) R. Br., Croton aromaticus L., Croton rotundus and Emilia sonchifolia (L.) DC. ex Wight except Emilia atrovirens were fully controlled when treated with 3/4 recommended trifloxysulfuron-sodium with sea water, 3/4 recommended trifloxysulfuronsodium with 3/4 sea water, 1/2 recommended trifloxysulfuron-sodium with sea water, 3/4 recommended quinclorac with sea water and 3/4 recommended quinclorac with 3/4 sea water. Eragrostis atrovirens (Desf.) Trin. ex Steud. exposed maximum (48%) injury when treated with 3/4 recommended trifloxysulfuron-sodium and sea water. Paspalum vaginatum Sw. showed only 8% injury to sea water in combination with 3/4 recommended quinclorac, indicating greater salt tolerance among the three turfgrass. Zoysia japonica Steud. also exposed no more than 14% injury when treated with sea water in combination with 3/4 recommended trifloxysulfuron-sodium or quinclorac. Cynodon dactylon (L.) Pers. 'Satiri' had up to 21% salt injury with 3/4 sea water in combination with 3/4 recommended trifloxysulfuron-sodium.